Implantable nano sensors - Sirivisoot, Sirinrath (Henry Stewart Talks, 2015)
Challenge of orthopedic implants, Rationale behind personalized medicine, Basic components of a closed-loop sensing and drug administration device, Development of in situ orthopedic sensor, Development of a voltage-controlled drug delivery coating, Future directions